siRNAs Targeting Mouse-Specific lncRNA AA388235 Induce Human Tumor Cell Pyroptosis/Apoptosis - Chen, Yan-Ru; Feng, Wan-Ying; Cheng, Yuan-Xiong; Zhu, Hao; Liu, Hong-Juan; Gao, Yi; Zhou, Wei-Jie (Frontiers in Oncology, 2021)
Species-specific lncRNAs significantly determine species-specific functions through various ways, such as epigenetic regulation. However, there has been no study focusing on the role of species-specific lncRNAs in other species yet. Here, we found that siRNAs targeting mouse-specific lncRNA AA388235 could significantly induce death of human tumor cells, although it has no effect on mouse tumor cells and normal human cells. The mechanism studies showed that these siRNAs could activate the response of human tumor cells to exogenous nucleic acids, induce pyroptosis and apoptosis in the presence of GSDME, but induce apoptosis in the absence of GSDME. They also significantly inhibited the growth of human tumor cells in vivo. 17 siRNAs were designed for seven more mouse-specific lncRNAs selected randomly, among which 12 siRNAs targeting five lncRNAs induced death in human tumor cell. Our study not only demonstrates that the siRNAs designed for knocking down mouse-specific lncRNA AA388235 can be potential tumor therapeutic drugs, but also suggests that non-human species-specific lncRNAs are a huge potential library that can be used to design siRNAs for tumor treatment. Large-scale screening based on this is promising.